(untitled) (Research, Society and Development, 2021)
To report the academic experience of a health education about dengue held in a state school in the city of Belém-PA. This is a qualitative and descriptive study, of the experience report type, reporting health education about dengue, developed in a state school in the city of Belém-PA, with the participation of 6th grade students, carried out by a multiprofessional team of undergraduates. The educational action was basically divided into two moments, the first was the one that brought students a more theoretical approach to dengue, and the other was characterized as a more practical moment. In the first moment and day of the action, the students were able to resolve their doubts and told their experiences and facts in relation to dengue after explaining the matter. The students also made a production of what was exposed by the undergraduates and in this production, it was noticeable to observe the creativity and learning of the students regarding the subject covered, because in the drawings, paintings, posters they made had aspects of dengue that were previously reported as, for example, the mosquito, where they can breed and others. In addition, there was the most practical moment of the action, where students dressed with PPE went in search of possible outbreaks of mosquitoes within the school environment. It is concluded then that a comprehensive look at the methodology showed that students will act as aims to dissipate preventive measures against dengue.